2019
DOI: 10.1097/aog.0000000000003216
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Prenatal Insomnia

Abstract: Cognitive behavioral therapy for insomnia is an effective treatment for prenatal insomnia disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 30 publications
7
101
1
6
Order By: Relevance
“…Given the potentially serious consequences of untreated anxiety and depression symptoms in pregnancy on physical and psychological outcomes, interventions are urgently needed to reduce symptoms and build resilience. Psychological interventions for preventing and treating depression and anxiety in pregnancy are effective, with cognitive behavior therapy (CBT) emerging as a front-line treatment and interpersonal therapy (IPT) potentially offering additional benefits to reduce depression and increase social support ( Field, 2017 ; Manber et al., 2019 ; O'Connor et al., 2019 ). Preliminary evidence also provides support for e-health interventions; however, trials to date are relatively small and scaling for widespread dissemination is urgently needed ( Felder et al., 2020 ; Heller et al., 2020 ; Loughnan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the potentially serious consequences of untreated anxiety and depression symptoms in pregnancy on physical and psychological outcomes, interventions are urgently needed to reduce symptoms and build resilience. Psychological interventions for preventing and treating depression and anxiety in pregnancy are effective, with cognitive behavior therapy (CBT) emerging as a front-line treatment and interpersonal therapy (IPT) potentially offering additional benefits to reduce depression and increase social support ( Field, 2017 ; Manber et al., 2019 ; O'Connor et al., 2019 ). Preliminary evidence also provides support for e-health interventions; however, trials to date are relatively small and scaling for widespread dissemination is urgently needed ( Felder et al., 2020 ; Heller et al., 2020 ; Loughnan et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antenatal insomnia is reported as a risk factor for experiencing insomnia postpartum (Dørheim et al, 2014). Hence, since cognitive behavioral therapy for insomnia (CBT-I) is not only associated with reduced symptoms of both insomnia and depression (Ballesio et al, 2017;Manber et al, 2019), but also reportedly safe and effective during pregnancy (Manber et al, 2018;Tomfohr-Madsen et al, 2017), it might improve symptoms of perinatal insomnia and depression when provided from mid-pregnancy on to women with insomnia, but more research on that topic remains necessary. Our results concerning associations between insomnia and depression did not differ significantly between primiparous and multiparous women, which suggests that parity plays a limited role in the interaction of perinatal sleep and mood (Coo Calcagni et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published randomized controlled trial showed that pregnant women randomized to undergo CBT-I experienced a significantly greater reduction in insomnia severity and faster remission of insomnia compared with women assigned to a control intervention. 41 Preliminary evidence from a small trial showed improvement in symptoms of depression, pregnancy-specific anxiety, chestjournal.org and fatigue, following treatment with CBT-I. 42 The impact of interventions to treat insomnia on maternal or fetal outcomes remains to be examined, however.…”
Section: Treatment Considerations For Insomnia In Pregnancymentioning
confidence: 99%